Evaluation of color stability of different esthetic restorative materials with whitening dentifrices - Iqbal Singh; Sai S Kalyan; Rakesh Kumar Gupta; Parveen Lone; Manisha Koul (Wolters Kluwer Medknow Publications, 2024)
Introduction: Color stability and surface roughness are important factors affecting the longevity of any restorative material, as a rough surface structure can lead to staining and discoloration. Aim: The aim of this study was to evaluate the effects of application of two over-the-counter whitening toothpastes (Colgate Optic White and Close-up) on the color stability of different esthetic restorative materials (resin composite and conventional glass-ionomer). Materials and Methods: Using Mylar strips, 120 specimens were created from each restorative material (resin composite and conventional glass-ionomer). Baseline color measurement was done. This was followed by brushing the specimens according to the groups were brushed with the different whitening toothpastes. Before measuring color, the samples were washed. Results: A significant color change was observed between the two restorative materials. The color change was significantly higher with Colgate Optic White than Close-up toothpaste. Furthermore, composite material showed higher color stability than glass-ionomer cement (GIC). Conclusion: When used for 2 min twice day for 15 days, the whitening toothpastes Colgate Optic White and Close UP do create noticeable changes in the color. Furthermore, composites showed higher favorability for color stability than GIC.